Analysis of the influence of pregnant women satisfaction on the motivation in compliance to antenatal care visits In Panti Community Health Centers, Jember Regency - Indah Muflihatin; Raden Roro Lia Chairina; Andri Permana Wicaksono (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2018)
Examination of Antenatal Care (ANC) is an examination of pregnancy to optimize the physical and mental health of pregnant women so they can face the birth, post-partum period, breastfeeding preparation, and restore the health of reproductive system naturally. Family planning, antenatal care, clean and safe vaginal delivery, and obstetric care should be applied to all women of reproductive age as stated in the Safe Motherhood with its concept of the four pillars. Utilization of health facilities needs to be improved to reduce morbidity and maternal mortality. As for the achievement of K1 and K4 coverage at Puskesmas Panti in the last two years remain below the target, namely K1 by 117%, while the K4 as much as 67.84%. In 2016, K1 coverage is equal to 414 (70.29%) of 589 pregnant women, K4 is as much as 38.54% of 227 pregnant women. These data indicate a considerable gap between the coverage of K1 and K4. The gap between K1 and K4 in Puskesmas Panti in 2016 is quite large, 31.75% of the target gap which should not exceed 10% (Data of PWS Puskesmas Panti, 2016). This study aimed to analyze the relationship between motivation and satisfaction levels of pregnant women in antenatal care at the Puskesmas Panti, Jember Regency. This research is quantitative research using path analysis method. This study design was cross-sectional with a sample of 50 pregnant women taken with the technique of consecutive sampling. Data were collected in August-November 2017. Data were analyzed using data processing software. The results showed that there was a positive relationship between satisfaction with patient motivation in conducting ANC with a value of CR 2.78, there was a significant effect between satisfaction with safety in conducting ANC with a CR value of 0.34, and there was satisfaction with non-support that increased the meeting patients in performing ANC with a CR value of 0.39.Furthermore, the results of the analysis and conclusions of the study will be the basis for solving health problems. The recommendation is provided based on results of the study as an attempt to improve the performance of K1 and K4. Keywords: Motivation ,  Satisfaction, Antenatal Care